Key Trends and Regulations of the Development of Digital business Models of banking services in Industry 4.0 - M. N. Dudin; S. V. Shkodinskii; D. I. Usmanov (Финансы: теория и практика, 2021)
The subject of the research is trends in the implementation of digital technologies in the banking sector. The relevance of the paper is due to the objective processes of global digital intervention of technologies in all spheres of human life and society. The research aims to identify, systematize and generalize key trends and regulations in the development of digital business models of banking services in Industry 4.0. For the first time, the authors identified and systematized modern trends and regulations in the development of digital business models of banking services in Industry 4.0, offered their own conceptual vision of the concept of “digital business model of banking services”. The authors apply general scientific, philosophical, analytical, statistical, problem chronological and historical-genetic methods, as well as methods of expert assessments. The article summarizes the main stages of the evolution of business models of the banking sector, reveals substantive and methodological differences between traditional remote banking services and digital banking, highlights the main business models for organizing digital banking; provides up-to-date data on the level of development of digital banking in the main geographic zones of the world; shows the dynamics and key areas of investment in the fintech industry in 2014–2019 and provides a critical analysis of their conditions; identifies problematic aspects of the development of digital business models of banking; describes the functionality of the main digital business models of Russian banks with the author’s assessment of their capabilities and examples of their use in Russian practice. The authors conclude that the main drivers of digitalization of the banking sector are stable growth of non-cash payments in the world and in Russia; stable growth of the global digital banking market; the impact of the COVID-19 pandemic on the active demand of consumers of remote financial services; increased competition in the retail banking market; and a significant decrease in margins for traditional banking products. Identification and systematization of trends and regulations in the implementation of digital business models of banking services can form the basis for further analysis of the specifics of digitalization and personalization of digital banking in Industry 4.0 for the sustainable socio-economic development of the country in terms of possible advantages and threats to the security of financial resources and personal data of customers.